Lifelong learning programmes - the choice of the community - UMP, PNC (2018)
KUANTAN- Universiti Malaysia Pahang's (UMP) lifelong learning programmes (PSH) should be given emphasis to help meet the demand for skilled human capital in this fast-moving world.